1970
DOI: 10.2323/jgam.16.6_543
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oxygen on Glucose Dissimilation by Heterolactic Bacteria

Abstract: It has been reported by several investigators that most strains of heterolactic bacteria are capable of utilizing oxygen and produce lactate, acetate, and carbon dioxide, as major products from glucose under aerobic conditions (1-5). This paper describes the remarkable effect of oxygen on glucose dissimilation in resting cells of heterolactic bacteria. All the organisms used in this study were grown under stationary conditions at 30° in a medium containing (in per cent), glucose, 2.0; anhydrous sodium acetate,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
9
1

Year Published

1971
1971
2000
2000

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 0 publications
1
9
1
Order By: Relevance
“…Although activities of NADH2 oxidase and NADPH2 oxidase were detected in the organism (9), it was previously reported that lactic acid formation by this organism was hardly affected by oxygen, while, under aerobic conditions, ethonol production decreased with a corresponding increase in acetate production indicating the existence of some mechanism of specific protection of lactic acid-forming system against the effect of oxygen ( 8 ). It is very interesting that ALDH and ADH of the organism were detected as insoluble enzymes suggesting the possibility of different localization of lactic acid dehydrogenase and glyceraldehyde 3-phosphate dehydrogenase from ALDH, ADH, NADH2 oxidase or NADPH2 oxidase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although activities of NADH2 oxidase and NADPH2 oxidase were detected in the organism (9), it was previously reported that lactic acid formation by this organism was hardly affected by oxygen, while, under aerobic conditions, ethonol production decreased with a corresponding increase in acetate production indicating the existence of some mechanism of specific protection of lactic acid-forming system against the effect of oxygen ( 8 ). It is very interesting that ALDH and ADH of the organism were detected as insoluble enzymes suggesting the possibility of different localization of lactic acid dehydrogenase and glyceraldehyde 3-phosphate dehydrogenase from ALDH, ADH, NADH2 oxidase or NADPH2 oxidase.…”
Section: Discussionmentioning
confidence: 99%
“…The metabolic pathway of ethanol production from acetyl phosphate in heterolactic fermentation has been believed to be ; acetyl phosphate-~acetyl-CoA-*acetaldehyde--ethanol (1 To clarify the mechanism of aerobic glucose dissimilation by heterolactic bacteria, on which some unexpected phenomena were reported, studies on basic characteristics of ALDH may be considered to be essential (8). During the course of studies on the purification of ALDH of Leuconostoc mesenteroides IFO 3426, we found that ALDH and ADH may be considered as enzymes associated with the same subcellular organelle.…”
mentioning
confidence: 99%
“…Furthermore, several strains of heterofermentation lactic 'acid bacteria have been shown to consume oxygen. 11 ) In .this .report, we report" the finding that several strains of P. halophilus consume a significant amount of oxygen in the presence of D-glucose Qr L-lactate" and also some charac-,teristicsof their oxygen consuming activity.…”
mentioning
confidence: 99%
“…In a previous work, however, we found that the resting cells of Lactobacillus brevis and L, buchneri, as well as pre-aerated resting cells of Leuconostoc mesenteroides, are unable to dissimilate glucose under stationary conditions, whereas they are capable of producing lactate, acetate, and a considerable amount of ethanol from glucose under shaking conditions (7). These phenomena seem unlikely to be explained by the mechanism described above, because semi-anaerobic (stationary) formation of ethanol was not detected, in spite of the fact that ethanol formation was observed even under aerobic conditions.…”
mentioning
confidence: 99%